Beyond Case Law: Kastom and Courts in Vanuatu - Forsyth, Miranda (Victoria University of Wellington Law Review, 2004)
This article considers the relationship between customary law (kastom) and the official legal system in Vanuatu. It looks at the limitations of the reasons propounded for the lack of integration of customary law and the official legal system and argues that the integration should be a two-way process. The author asserts that a new methodological approach is required to assess the issue regarding the current extent of integration, desirability of integration and capacity for integration of the two systems. Rather than merely analysing case law or legislation, the author argues that the reality behind this picture needs to be investigated and empirical research undertaken.